The Effect of Emotional Intelligence, Work Attitude and Work Motivation on The Promotion of Pegawai Position in The Environment of The Directorate General of The Potential of Defense of The Ministry of Defense, RI - Subagio, Mochammad (IJHCM (International Journal of Human Capital Management), 2024)
The purpose of this study was to determine the effect of Emotional Intelligence, Work Attitude, and Work Motivation on the Employees Job Promotion of the Directorate General of Defense Potential of the Ministry of Defense The number of samples in this study was 90 people who was employees of the Directorate General of Defence Potentials, Ministry Of Defence RI. The technique of data analysis used was descriptive statistics and multiple linear regression analysis. The measurement in this study was done by giving the value of each statement item from all variables using a Likert scale. The result of data questionnaire were analyzed, such as: description of data, testing of research requirements, including normality test, homogeneity test, and linearity test. In order to prove the influence of variables on this study, it was implemented by the techniques of data analysis with path analysis. The conclusion of the results of this study could be stated : partially emotional intelligence had a significant effect on promotion, meaning that if emotional intelligence is better, it will lead to greater opportunities for employees to be promoted to higher positions. The attitude of work had a significant effect on promotion, meaning that if an improved work attitude would lead to an increase in the chances of an employee for promotion. Work motivation has a significant effect on promotion, meaning that if the quality of work motivation was high, the opportunity for promotion was greater. While simultaneously emotional intelligence, work attitudes, and work motivation had a significant effect on the promotion of the employee's position at the Directorate General of Defence Potential, Ministry of Defence RI.